Optimizing Village Sustainability, Village Funds, And Tourism Strategic Plan For Household Welfare In The Coastal Area Of South Nias Regency - Ahmad Jumadin Gulo; M. Wahyu Shihab; Irsad Lubis (UNIVED Press, 2025)
This research is motivated by the implementation of the Sustainable Development Goals (SDGs) applied by the central government to regions up to the village level, through programs tailored to local conditions. Sustainable development is expected to reduce inequality between villages and cities. However, its implementation in South Nias Regency still faces obstacles, especially in the allocation of village funds that have not had a significant impact on the development and economy of the community. This problem is related to politics, unilateral policies, and the slow process of fund disbursement, which has led to community complaints due to the lack of income and support from the government. The research was conducted in Botohili Sorake Village, with the aim of analyzing the influence of Village SDGs, Village Funds, and Tourism Strategic Plan on tourist visits and household welfare. The research sample consisted of 200 households with data collected through questionnaires and analyzed using the SEM (Structural Equation Modeling) method with Amos version 23.0 software. The results showed that the variables of Village SDGs, Village Fund, and Tourism Strategic Plan had a significant effect on tourist visits. However, only the Tourism Strategic Plan has a significant effect on household welfare, while the Village SDGs and Village Fund do not. This study recommends that the government manage village funds wisely and transparently, and support infrastructure development and tourism promotion. In addition, it is important to work with educational institutions to improve people's understanding of the SDGs, which can ultimately improve their welfare.